IoT-enabled user agency for building sustainability - Lee, Stephen; Dieng, Ousmane; Shangguan, Longfei; Biehl, Jacob; Lee, Adam; Mossé, Daniel; Chrysanthis, Panos K. (Frontiers in the Internet of Things, 2023)
Buildings are a significant source of greenhouse gas emissions, and many organizations recognize that reducing commercial building-related emissions is crucial to achieving a carbon-neutral future. However, leveraging state-of-the-art building energy-efficiency techniques can be expensive and require installing new equipment, resulting in only a small percentage of energy-efficient commercial buildings. To address this challenge, our paper focuses on empowering building occupants to become informed change-makers that drive building efficiency through an IoT-based solution. We propose using low-cost IoT sensors to collect data on occupied and shared spaces in commercial buildings. This data will be used to create a personalized dashboard for each individual, increasing transparency and helping people understand how they can use space more efficiently while reducing emissions. To further optimize energy and emissions, we will leverage human flexibility through targeted interventions. Finally, our platform will suggest specific actions that individuals can take to improve their space usage and reduce their environmental impact. By enabling human-building interaction, we envision our approach will be more effective in achieving the full potential of reducing energy and emissions in existing buildings.